PENGARUH IKLAN POKKITS TERHADAP KEPUTUSAN PEMBELIAN PADA KONSUMEN KENTUCKY FRIED CHICKEN CABANG SUN PLAZA MEDAN - Stephanie Harefa; Fivi Sofiyah (Jurnal Media Informasi Manajemen, 2013)
The main function of advertising is to communicate an information as efficient as possible to the hundreds thousands of people in number. In its activities, it does the most important economic function for the advertisers and audiences. In many cases, introducing new products will not be done easily if the advertising can not tell people about the product. The purpose of this study was to determine and analyze the effect of Pokkits on television advertising on Consumer Buying Decision against Kentucky Fried Chicken of Sun Plaza Medan’s Branch. Data used in this study are primary and secondary data. Primary data was obtained by using questionnaire. Secondary data was obtained from documentary studies of literature, journals, magazines, and web page relevant to the study. Data analysis method used in this study is a simple regression analysis method. Population in this study is all consumers of Kentucky Fried Chicken of Sun Plaza Medan’s Branch who ever bought Pokkits and ages between 12-35 years old. Using prediction interval formula where the total sample used in this study is rounded up to 97 people. The sampling method used in this study is judgment sampling. The results showed that the television advertising of KFC Pokkits has positive and significant impacts on consumer purchasing decision against KFC of Sun Plaza Medan’s Branch.   Keywords: Television Advertising and Purchasing Decision